A Meta-Analysis of Outcomes After In Situ Reconstructions for Aortic Graft Infection. (May 2018) - Batt, Michel; Feugier, Patrick; Camou, Fabrice; Coffy, Amandine; Senneville, Eric; Caillon, Jocelyne; Calvet, Brigitte; Chidiac, Christian; Laurent, Frederic; Revest, Matthieu; Daures, Jean Pierre; ,
Objective: To confirm the advantage of in situ reconstruction (ISR) over extra-anatomic reconstruction (EAR) for aortic graft infection and determine the most appropriate conduit including autogenous veins, cryopreserved allografts, and synthetic prosthesis (standard, rifampicin of silver polyesters). Methods: A meta-analysis was conducted with rate of mortality, graft occlusion, amputation, and reinfection. A meta-regression was performed with 4 factors: patients' age, presence of prosthetic-duodenal fistula (PDF), virulent organisms, or nonvirulent organisms. Results: In situ reconstruction over EAR seems to favor all events. For the 5 conduits used for ISR, according to operative mortality, age of the patients looks to have a positive correlation only for silver polyester and no conduit present any advantage in the presence of PDF. Reinfection seems to be not significantly different for the 5 conduits, and only autogenous veins appear to have a positive correlation with infecting organisms. Conclusion: In situ reconstruction may be considered as first-line treatment. Our results suggest that silver polyesters appear to be most appropriate for older patients, and in order to limit reinfection, autogenous veins are probably the most suitable conduit.